Creatine supplementation delays onset of fatigue during repeated bouts of sprint running - Aaserud, R.; Gramvik, P.; Olsen, S. R.; Jensen, J. (Scandinavian Journal of Medicine & Science in Sports, 1998)
In this study we have investigated the effect of creatine supplementation on performance of repeated sprint runs in well-trained young male handball players. The subjects participated in a test before supplementation (T1) and then received creatine (15 g/d) or placebo for five days before a second test was carried out (T2). Following T2, a low dose of creatine (2 g/d) or placebo was maintained for an additional nine days before the third test was performed (T3). The tests consisted of eight 40 m maximal sprint runs with a 25-s rest period between each sprint. Run time was reduced on the last three sprint runs after five days with high doses of creatine supplementation compared to T1 (P < 0.05). Although the run time during the last three sprints was still significantly lower after supplementation of low doses of creatine compared to T1, analysis of variance showed only a tendency for an interaction between test day and random group (P = 0.14). No improvement was seen in the placebo group. Blood lactate was similar at T1 and T2 in the creatine and placebo groups. In conclusion, high doses of creatine supplementation improve performance during repeated sprint runs in well-trained handball players. Further studies are needed to clarify whether low doses of creatine supplementation, after a period with supplementation of high doses, are able to maintain improved performance.